Spiritual Well-Being and Optimism as Contributing Factors that Influence the Subjective Well-Being of Cancer Patients - Yesiana Dwi Wahyu Werdani (Indonesian Journal of Cancer, 2022)
Background: Cancer is a serious stressor that induces spiritual distress, loss of optimism, and dissatisfaction with subjective well-being. This study aims to determine that spiritual well-being (SWB) and optimism as factors that contribute to influencing the subjective well-being of cancer patients. Methods: This study had a cross-sectional design. A total of 88 cancer patients from public health centers in Surabaya and the Indonesian Cancer Foundation of East Java were selected to be sampled by consecutive sampling in 4 months. The Instruments used were valid and reliable throughout the test, comprising of the spiritual well-being scale, the 9-item version of the personal optimism scale, self-efficacy optimism scale, and satisfaction with life scale. The ethical feasibility was declared ethical. Data were analyzed using Pearson Product Moment Correlation Test and Linear Regression Test with p < 0.05. Results: The demographic data show that the mean age of 52.5 years, female gender (84%), being married (78.4%), having cervical cancer (52.3%), having stage-III cancer (55.7%), having cancer therapy (surgery, chemotherapy, and radiotherapy) (37.5%), and patients newly diagnosed from 6 months to 1 year (33%). The mean score of SWB was 99.67 (high SWB), optimism 20.03 (high optimism), and subjective well-being 24.18 (good subjective well-being). Pearson Product Moment Correlation Test between SWB and optimism showed p < 0.001, indicating that SWB had a significant relationship with optimism; patients with high SWB will have high optimism. From the Linear Regression Test, there was a significant effect of SWB on subjective well-being (r2 = 0.982 and p < 0.001) and optimism on subjective well-being as well (r2 = 0.988 and p < 0.001), meaning that patients with high SWB and high optimism tended to have good subjective well-being.  Conclusions: Cancer patients who have high scores of SWB become more optimistic, which has a positive effect on the high score of subjective well-being as well.